EFEKTIVITAS PROGRAM BANTUAN KEUANGAN KHUSUS PADA BADAN USAHA MILIK KAMPUNG (BUMKAM) TANDAN SEJATI DI KAMPUNG BANJAR SEMINAI KECAMATAN DAYUN KABUPATEN SIAK TAHUN 2019-2022 - Dayuningtias, Naomi Fauziah; ', Adlin (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2024)
The Riau provincial government has specifically provided village development support through financial transfers from the Riau Provincial Government to Villages in the form of Special Financial Assistance (BKK) from the Riau Provincial Government to Villages since 2019. In Governor Regulation Number 39 of 2022 article 3 paragraph 7 explains that Assistance Special finance is provided on the basis of the Province's capabilities to support the Province's strategic policies and/or national programs in accordance with matters under the authority of the Regency/City. BUMKam Tandan Sejati is one of the recipients of Special Financial Assistance from the Provincial Government, BUMKam Tandan Sejati received assistance in the form of capital participation. The capital participation assistance was used to open a tent and waserda rental business unit. The aim of this research is to find out how effective the special financial assistance program is for the Tandan Sejati village-owned business entity (BUMKam) in 2019-2022. This research uses a qualitative approach with descriptive methods. The author used interview and documentation techniques to collect data. This research uses the theory put forward by Edy Sutrisno and Hasibuan to measure the effectiveness of program effectiveness, Program Understanding, Apparatus Quality, Right on Target, On Time, Achievement of Goals, Facilities and Infrastructure, supervision. The results of this research concluded that the effectiveness of the special financial assistance program at BUMKam Tandan Sejati was based on effectiveness measures. Achieving the objectives was not yet fully effective because the community had not fully felt the benefits of the business units being run due to the lack of environmental targets for developing business units and the existence of competition. Keywords: Effectiveness, Special Financial Assistance, BUMKam Tandan Sejati